Teaching user-friendly web design : a case study on zillow.com in the real estate industry - Manko, Barbara (London : Journal of Information Technology Teaching Cases, 2021)
When designing websites and planning marketing concepts, students need to understand how to create an experience that is user-friendly in order to build traffic over time. Users want a website that is both intuitive and informative, while simultaneously providing an ultra-efficient search experience. They want information that is essential and specific to them, for their own precise needs and purposes. The key to designing a successful interface is to meet the user's expectations of finding a suitable fact, product, or service expeditiously. Examining the case of Zillow.com, a highly successful real estate portal website, provides students with an effective example of underlying web design principles, such as user knowledge, ease of navigation, content adjustment, and the site's fit within the digital marketplace. Zillow.com exemplifies incredible ease of use through various aspects of superior web design, such as the accessibility and functionality of both of the top menu and submenu links and the ability to filter search results using data fields with key requirements, leading to instant, valuable results. By looking at what Zillow has done right, students can glean a set of best practices in web design that not only apply to the real estate industry, but can be translated broadly across websites in all industries.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Web sites -- Design -- Study and teaching -- Case studies; Internet access -- Case studies